2018
DOI: 10.1016/j.cellimm.2017.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Infection of hematopoietic stem cells by Leishmania infantum increases erythropoiesis and alters the phenotypic and functional profiles of progeny

Abstract: Immunosuppression is a well-established risk factor for Visceral Leishmaniasis. Post-immunosuppression leishmaniasis is characterized by an increase of parasite burden, hematopoietic disorders and unusual clinical manifestations. Although there are many reports on bone marrow findings in VL, less is known about the relationship between parasite dynamics in this organ and the function of either hematopoietic stem cells and progenitor cells themselves. In the present study, we tackle these issues using a new app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Recent studies showing the uptake of L. donovani/L. infantum parasites in human (Carvalho-Gontijo et al, 2018) and murine HSCs (Dirkx et al, 2022) further validates our results obtained by dual scRNA-Seq analysis. Our in vivo studies from Balb/C mice that has been infected with L. donovani DsRed parasites for 9 months showed that Ter-119-CD11b-CD45R-CD5-CD3-Gr1-Sca-1+c-Kit+ HSCs remain infected with the parasites strengthens the hypothesis that HSCs maybe a source of persistent infection due to their longevity.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies showing the uptake of L. donovani/L. infantum parasites in human (Carvalho-Gontijo et al, 2018) and murine HSCs (Dirkx et al, 2022) further validates our results obtained by dual scRNA-Seq analysis. Our in vivo studies from Balb/C mice that has been infected with L. donovani DsRed parasites for 9 months showed that Ter-119-CD11b-CD45R-CD5-CD3-Gr1-Sca-1+c-Kit+ HSCs remain infected with the parasites strengthens the hypothesis that HSCs maybe a source of persistent infection due to their longevity.…”
Section: Discussionsupporting
confidence: 88%
“…In a study by Pinto et al that did not include a progenitor enrichment 19 , no infected LT-HSC were detected after 28 days of infection with Td-Tomato transgenic L. donovani . In contrast, an in vitro study by Carvalho-Gontijo et al 68 documented the presence of L. infantum in human CD34 + stem cells. According to Cotterell et al 69 , CD34 + progenitor cells do not appear to be targets for Leishmania infection.…”
Section: Discussionmentioning
confidence: 90%
“…The authors further con rmed the parasite's viability highlighting the importance of the BM stroma during VL infection. A study by Carvalho-Gontijo et al [43] also documented the presence of L. infantum in human CD34+ stem cells. Our study further pinpointed the exact cellular tropism in the various stem cell and progenitor subsets.…”
Section: Discussionmentioning
confidence: 89%